Code-Switching and the Linguistic Identity in Ilias Khoury’s Gate of the Sun - Hussein, Amani Mehdi (Al-Adab Journal, 2020)
Code-Switching is the capacity of a bilingual individual or a multilingual individual to utilize more than one language instantly to serve the current purpose. Though most sociolinguists see that the reason behind using code switching is the lexical need, i.e. to fit in, to get something, or because of lizard brain, it is the issue of identity that makes many speakers code switch. The present paper investigates the cases of code switching in Khoury’s Gate of the Sun and the reason behind that is also to shed light on the translated version of the novel and the short comings of code switching in the translation. Hence, the present paper has devoted a reference to the mistakes found in the process of translating the text. The findings show that it is the case of the linguistic identity stands behind making many characters code switch, not because they miss the suitable word, but rather they are more likely to express their linguistic identity.